FINANCIAL RATIO ANALYSIS ON PROFIT GROWTH AND STOCK RETURNS IN RAW MATERIAL SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
This research aims to examine the effect of Return on Assets, Net Profit Margin, Debt to Equity Ratio and Total Assets Turn over on Profit Growth and Stock Return at basic materials sector companies listed on the Indonesia Stock Exchange in 2016-2021. This study uses secondary data. The sampling technique used in this study is purposive sampling. The number of samples obtained were 26 companies. The analysis method of this research is descriptive analysis and several types of evaluation using SmartPLS software. Based on this research, it can be concluded that Return on Assets have negative and significant effect on Profit Growth, Net Profit Margin have positive and significant effect on Profit Growth, Debt to Equity Ratio and Total Assets Turn Over have no significant effect on Profit Growth. Return on Assets, Net Profit Margin, Debt to Equity Ratio and Total Assets Turn Over have no significant effect on Stock Return, Profit Growth have positive and significant effect on Stock Return.